Pengaruh Edukasi Kesehatan Terhadap Pengetahuan Ibu Tentang Pencegahan Stunting Pada Balita di Posyandu Anggrek Wilayah Kerja Puskesmas Wara Kota Palopo - Kartini S; Eka Fadillah Bagenda; Hartati S (Pusat Riset dan Inovasi Nasional, 2025)
Stunting is an indicator of chronic nutritional problems that requires serious attention for the growth and development of children, especially toddlers. Low maternal knowledge about stunting prevention is one of the main risk factors that can worsen this condition. This research aimed to assess the impact of health education on enhancing mothers' knowledge about stunting prevention. The study took place in the Wara Public Health Center area, Palopo City, from May to June 2025, employing a quantitative method with a pre-experimental design using one group and pretest-posttest measurements. A total of 57 participants were included as research subjects. Data collection was carried out using questionnaires, and the Wilcoxon Signed Rank Test was utilized for analysis. The findings demonstrated a notable improvement in mothers' knowledge after the health education intervention, with most respondents falling into the category of having good knowledge. Statistical analysis yielded a p-value of less than 0.05, confirming that the health education significantly enhanced mothers' knowledge. These findings suggest that appropriate educational interventions can serve as an effective strategy in preventing stunting within the community. Therefore, strengthening health education programs, especially at the primary care level such as integrated health posts (posyandu), should be continuously optimized to enhance awareness and preventive behaviors among mothers.